The Role of Religions in Education of Ethics of Diversity - Monia, Naffati Gharbi (Unisia, 2023)
This article explores the role of religions in fostering an ethos of respect for diversity and cultivating the ethics of constructive disagreement. Recognizing that diversity is an inherent trait of human existence, this study highlights the necessity of transcending conflict and cultivating harmony through a moral framework derived from religious principles. Using key religious texts and examples, the paper analyzes the doctrines and practices of Hinduism, Buddhism, Judaism, Christianity, and Islam, demonstrating their contributions to peacebuilding and intercultural understanding. Hinduism and Buddhism emphasize values of self-realization, meditation, and universal love, fostering the ability to transcend individual differences. Judaism advocates ethical principles, such as justice and integrity, while distinguishing between religious teachings and political ideologies. Christianity, particularly through its message of love and forgiveness, offers a model for reconciliation with one’s adversaries. Islam’s foundational principles, including equality, tolerance, and respect for freedom of belief, provide a legal and moral framework for coexistence and dialogue, epitomized by the Prophet Muhammad’s ethical treatment of diverse communities. Through these religious paradigms, the study addresses the challenges of ideological extremism, historical grievances, and structural inequalities that hinder peaceful coexistence. It proposes practical strategies for embedding the ethics of disagreement within educational, legal, and social institutions. The findings underline the urgency of interfaith collaboration and the application of shared values to overcome global crises of conflict and division, advocating for a collective moral responsibility that transcends cultural and theological boundaries. This discourse reaffirms the enduring relevance of religions in shaping a harmonious global society.